The Influence of Climate Change on Rainfall and Rainy Days for Rubber Production of Kusen Clone in Rambang District, Muara Enim Regency - Andika, Eva Juniar; Rejo, Amin; Puspitahati (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Extreme rainfall impacts rubber production, reducing effective tapping days and cumulative annual output and having a wide-ranging effect on rubber crop cultivation. This study aimed to find out how rainfall and rainy days affected the rubber production of the Kusen clone in Muara Enim Regency’s Rambang District. The study was conducted on a rubber plantation of Kusen clone, which has an area of 1 ha. The initial stage in analyzing the impact of climate change on Kusen clone rubber production in Rambang District, Muara Enim Regency, was identifying the independent and dependent variables. The T-test was conducted to see whether each independent variable partially has a significant effect on the dependent variable. Rubber production has fallen year after year, with an average of 205.12 kg/ha in 2019 during the first year of tapping and 118.43 in 2023. The coefficient value (r) shows a 27.2% (sufficient correlation) magnitude association between the rainfall and rainy-day variables and the rubber productivity variable of the Kusen clone. In Correlation test results, rainfall and rainy days are strongly associated with producing Kusen clone rubber, as demonstrated by the correlation analysis value of 0.846. Regression research showed that rainfall and rainy days had a statistically insignificant effect on rubber production on the rubber clone Kusen in Rambang District, Muara Enim Regency.